2010
DOI: 10.1097/prs.0b013e3181c2a685
|View full text |Cite
|
Sign up to set email alerts
|

Aging of the Mandible and Its Aesthetic Implications

Abstract: These results suggest that the bony elements of the mandible change significantly with age for both genders and that these changes, coupled with soft-tissue changes, lead to the appearance of the aged lower third of the face.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
109
5
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(123 citation statements)
references
References 20 publications
4
109
5
5
Order By: Relevance
“…[13] In each three studies; the mean of bigonial width in men was greater than in women. [13,14,15] DOI: 10.9790/0853-1507108287 www.iosrjournals.org 86 | Page…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[13] In each three studies; the mean of bigonial width in men was greater than in women. [13,14,15] DOI: 10.9790/0853-1507108287 www.iosrjournals.org 86 | Page…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, many recent studies suggest that the bone aging of the facial bone is a process primarily of contraction and morphologic changes. [7,8,11]In a study which was carried out by Shaw et al on 3D CT images, it was revealed that there were no significant changes in bigonial width and ramus breadth across ages in both genders. Ramus height, mandibular body height and mandibular body length decreased with age for both genders and mandibular angle increased in both genders across ages.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…De wangen vlakken af en gaan plooien en de nasolabiale plooi wordt dieper. De lippen lijken dunner door de afname van het lippenrood (Mohindra en Bulman, 2002;Pecora et al, 2008;Shaw et al, 2010). Omdat de huid meer gaat hangen en de spiermassa minder wordt, worden met de tijd de incisieven in de bovenkaak minder zichtbaar en de incisieven in de onderkaak juist meer.…”
Section: Belang Van Verticale Dimensieunclassified